Pengujian Logam Berat pada Tanah Terkontaminasi Air Limbah PLTD di Petung, Kalimantan Timur - Intan D W S Rini; Adrian Gunawan; A. Ibnu Arobi (SPECTA Journal of Technology, 2018)
PLTD (Pembangkit Listrik Tenaga Diesel) Petung or PLTD Girimukti is located in North Penajam Paser District, East Kalimantan Province which is the capacity of 2 x 1.0 MW. Wastewater sewerage that passed through oil palm plantations and settlements made water and soil pollution. Result of water test and soil fertility showed that there is no parameter of environmental control is higher than quality standards (PP No 101 Tahun 2014). The aim of TCLP (Toxicity Characteristic Leaching Procedure) testing is knowing the content of heavy metal in the soil. TCLP method is USEPA 3050B-96. The several heavy metals parameters are Ag, Hg, As, Zn, Pb, Cu, B, Ba, Cd, Cr, and S. The result showed that the content of these heavy metal are lower than quality standard. This indicated that the land and oil palm plantations were not polluted by heavy metals.